2002
DOI: 10.1270/jsbbs.52.275
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci for Nonstructural Carbohydrate Accumulation in Leaf Sheaths and Culms of Rice (Oryza sativa L.) and their Effects on Grain Filling.

Abstract: Quantitative trait loci (QTLs) that affect the accumulation of nonstructural carbohydrates (NSCs) in the leaf sheaths and culms of rice (Oryza sativa L.), enhancing subsequent grain filling, were analyzed in a population of back-crossed inbred lines (BCILs) from the cross Sasanishiki (japonica)/Habataki (indica)//Sasanishiki/// Sasanishiki. QTLs affecting NSC accumulation were detected on chromosomes 1, 4, 5, 7, 11 and 12. Of these, the indica alleles of QTLs on chromosomes 7 and 12 increased NSC accumulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 30 publications
0
31
1
Order By: Relevance
“…The collinear region in rice chromosome 12 includes several Xowering QTLs (Mei et al 2003;Nagata et al 2002;Septiningsih et al 2003;Uga et al 2007). However, it is currently not possible to determine whether Vrn-D4 corresponds to any of these rice QTL, because the arm location of Vrn-D4 in wheat is not yet known, and therefore, the colinear region in rice chromosome 12 is too large.…”
Section: Vrn-d4 Mappingmentioning
confidence: 99%
“…The collinear region in rice chromosome 12 includes several Xowering QTLs (Mei et al 2003;Nagata et al 2002;Septiningsih et al 2003;Uga et al 2007). However, it is currently not possible to determine whether Vrn-D4 corresponds to any of these rice QTL, because the arm location of Vrn-D4 in wheat is not yet known, and therefore, the colinear region in rice chromosome 12 is too large.…”
Section: Vrn-d4 Mappingmentioning
confidence: 99%
“…However, current knowledge of wheat is limited. In other crop species, WSC is a quantitative trait (Galiba et al 1997;Teulat et al 2001;Nagata et al 2002;Takai et al 2005;Thévenot et al 2005). Molecular quantitative genetics is a useful approach for studying complex quantitative traits by describing the characteristics of continuous phenotypic distributions and for estimating the number of loci involved, the average gene action, and the degree of interaction between quantitative trait loci (QTL) and environment (Tanksley 1993).…”
mentioning
confidence: 99%
“…Nagata et al (2002) found QTLs for NSC concentration in leaf sheaths and culms on chromosome 5 and 11 but not on chromosome 10 using Sasanishiki/Habataki BILs population. NSC in the culms and leaf sheaths at heading might be controlled mainly by the balance of starch and sucrose metabolism including sucrose transport.…”
Section: Discussionmentioning
confidence: 85%
“…Previously, QTLs for RuBisCO content (Ishimaru et al, 2001) and NSC concentration (Nagata et al, 2002) have been studied using segregated populations which include epistasis under the complex gene interactions. However, those reports were still far from practical use of QTLs directly toward the development of valuable near isogenic lines (NIL).…”
mentioning
confidence: 99%